THE INFLUENCE OF SCOUTING EDUCATION, ORGANISATIONAL EXPERIENCE, ON SKILLS AND ITS IMPLICATIONS ON SCOUT LEADER PERFORMANCE IN MENES DISTRICT, PANDEGLANG REGENCY - Yayah Sunariah; Tata Rustandi; Angrian Permana (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Scouting education is part of the national education system and plays a vital role in shaping students' character, skills, and personality through a systematic, continuous development process. Scouting not only functions as an extracurricular activity, but also as a non-formal educational vehicle that supports the national education goal of developing people who are faithful, moral, independent, and possess life skills. In this context, the quality of development is greatly influenced by the competence and performance of scout leaders. This study aims to analyse the influence of scouting education and organisational experience on skills and their implications for the performance of scout leaders in the Menes District, Pandeglang Regency. The study used a quantitative, explanatory design. Data were collected through questionnaires from 98 scout leaders who served as respondents using a saturated sampling technique. Data analysis was conducted using Structural Equation Modelling based on Partial Least Squares (SEM-PLS). The results showed that scouting education and organisational experience had a positive, significant effect on scout leader skills. In addition, scouting education, organisational experience, and skills significantly affected scout leader performance. Skills have been shown to have the strongest influence on performance and to mediate the relationship between scouting education and organisational experience on scoutmaster performance. These findings indicate that improved scoutmaster performance is not solely determined by education and organisational experience, but also by strengthening skills relevant to the coaching task. Therefore, developing sustainable scouting education, increasing organisational involvement, and strengthening scoutmaster skills programs are important strategies to improve the quality of scouter training in educational units.